Modified DLLME-SFO approach for evaluation of multiclass agrochemicals and its associated risk assessment: Soil, Saccharum officinarum and Jaggery. (October 2022) - Yadav, Priyanka; Singh, Ravi; Gupta, Neha; Kumar, Sandeep; Thakur, Ravindra Singh; Khan, A.H.; Ansari, Nasreen Ghazi; Patel, Devendra Kumar
Highlights: A corroborative modified DLLME-SFO method for simultaneous determination of multi-residue pesticides in soil, sugarcane and jaggery was developed and established using GC-µECD. Multivariate analysis is performed for further validation of the concentration of pesticides obtained in the matrices and correlation study establish the relation between the transfer of pesticides between soil and saccharum officinarum . Dietary and ecological soil risk assessment of multi-residue pesticides implies that the concentration of pesticides detected lies in acceptable range for soil organisms but have negative effects on human population on consumption of raw sugarcane and jaggery. The carcinogenic risk assessment places children to be in more danger zone on consumption of raw sugarcane than adults. Abstract: Pesticides have drawn attention due to their presence in various matrices and thus its after-effects in the environment and human body via various pathways. The use of agrochemicals by farmers in developing countries up-surged because of their low cost that results in increased production of crops. In the present study, a modified DLLME-SFO method was developed, optimized, and validated in soil, sugarcane, and jaggery. The developed method provides recoveries between 59.5- 109.48% and RSD less than 10% for all the analytes. The current study focuses on associated human dietary risk assessment on consumption of raw sugarcane and jaggery poses major threat to children and supports the concept that risk is age-dependent. In chronic exposure, pesticides detected were alachlor and heptachlor that have the potential of causing cancer. The risk to the soil ecology is within the acceptable range indicating the direct application of pesticides to crops rather than soil. Graphical abstract: Image, graphical abstract